2018
DOI: 10.1371/journal.pone.0203332
|View full text |Cite
|
Sign up to set email alerts
|

The nasal oxygen practice in intensive care units in China: A multi-centered survey

Abstract: BackgroundNurses frequently administer nasal oxygen therapy for patients in intensive care units (ICUs). However, little is known about the current status, nurses’ management and perception on the nasal oxygen therapy in China. Therefore, we aimed to investigate the nasal oxygen practice of ICUs in China to provide insights into future direction.MethodsA cross-sectional survey on 10 hospitals was conducted. A self-designed questionnaire was administered to ICU nurses. Descriptive statistics, univariate, and mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…Evidence showed that education improves the knowledge regarding oxygen administration 10 , and in addition to nurses, the majority of medical doctors were included in a study conducted in Nigeria. However, the current study nding is lower than a study conducted in China (58.28%) 11 . Studies revealed that knowledge of oxygen therapy varied because of several problems including lack of training on oxygen therapy, due to the absence of written guideline s12 , formation of new policies and, procurement and maintenance of oxygen administration activities in developed countries 13 .…”
Section: Discussioncontrasting
confidence: 87%
“…Evidence showed that education improves the knowledge regarding oxygen administration 10 , and in addition to nurses, the majority of medical doctors were included in a study conducted in Nigeria. However, the current study nding is lower than a study conducted in China (58.28%) 11 . Studies revealed that knowledge of oxygen therapy varied because of several problems including lack of training on oxygen therapy, due to the absence of written guideline s12 , formation of new policies and, procurement and maintenance of oxygen administration activities in developed countries 13 .…”
Section: Discussioncontrasting
confidence: 87%
“…Currently, the low‐flow oxygen delivery by the nasal cannula is routinely humidified clinically with cold bubble water in China (Wen et al, ), and at present, the textbooks of nursing education in China still recommend the use of cold bubble water for low‐flow oxygen humidification (Ma & Miao, ); however, several recent studies (Sun, Zhang, & Cheng, ; Wen et al, ) have concluded that it is unnecessary to humidify the low‐flow oxygen routinely. Besides, the most related researches are conducted in adult population, the studies in the children population are very rare.…”
Section: Discussionmentioning
confidence: 99%
“…The nasal oxygen delivery is very common in clinical setting, especially in the paediatric intensive care unit (PICU), with a usage rate of 92.6% (Wen et al, ). The oxygen delivered by the nasal canal is generally low flow, and it can increase the blood oxygen content of the arteries, correct the hypoxic state of body and improve the prognosis of patients (Kourouche, Buckley, Munroe, & Curtis, ; Wittenstein, Ball, Pelosi, & Gama de Abreu, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] Most European and North American countries use nonhumidified oxygen for low-flow oxygen, while China and Japan still often perform humidified oxygen in clinical practice. [5] The results of previous surveys [6,7] have showed that 84.48% of clinical nurses in China will perform humidification in oxygen supply regardless of the oxygen flow rate. At present, there are still big differences in humidification management in clinical nursing practice amongst different countries.…”
Section: Introductionmentioning
confidence: 99%